A Feasibility Study of a Remotely-Delivered Mindfulness-Based Training for Adolescents During the COVID-19 Pandemic - Tymofiyeva, Olga; Hu, Melody Y.; Sipes, Benjamin S.; Jakary, Angela; Glidden, David V.; Jariwala, Namasvi; Bhandari, Sarina; Parks, Kendall C.; Nguyen, Ca; Henje, Eva; Yang, Tony T. (Frontiers in Psychiatry, 2022)
Social distancing, home confinement, economic challenges, and COVID-19-related illness and deaths during the COVID-19 pandemic can significantly affect mental health in youth. One promising approach to reduce anxiety and depression in adolescents is the neuroscience-based mindfulness intervention Training for Awareness, Resilience, and Action (TARA). The objective of this individually randomized waitlist-controlled trial (RCT) was (1) to test the feasibility of TARA, delivered partially over Zoom, and (2) to assess changes in the emotional wellbeing in healthy adolescents between the ages of 14–18 years old during the COVID-19 pandemic. Methods: Twenty-one healthy adolescents were randomized to the TARA intervention or to the waitlist control group in February 2020, just before the start of the pandemic. The TARA group intervention was delivered in person for the first five sessions and remotely over Zoom for the remaining seven sessions due to the pandemic. The participants’ acceptability of TARA was assessed weekly using the Child Session Rating Scale (CSRS). The primary outcome was the emotional wellbeing measured using emotional symptoms subscale of the Strengths and Difficulties Questionnaire (SDQ) pre/post-TARA. We also explored weekly changes in TARA participants’ wellbeing using the Child Outcome Rating Scale (CORS). Results: The overall session rating in TARA participants improved after the switch to Zoom (Cohen’s d = 1.2, p = 0.008). The results of the two-way ANOVA showed no statistically significant difference in the change of the SDQ emotional symptoms during the 12 weeks between the TARA group and waitlist-control group (timepoint × group interaction: F = 0.77, p = 0.38). The exploratory analysis using the CORS in the TARA participants showed a significant improvement in their functioning over the weeks of training. Conclusion: Our results support the feasibility of TARA delivered over Zoom. While our primary outcome did not provide support for the improvement of the emotional wellbeing with TARA compared to a passive control group, our exploratory analysis in the intervention group indicated an improved functioning over the weeks of TARA training. The important general positive impact of this study lies in the possibility of offering a neuroscience-based mindfulness intervention remotely to youth living in remote areas and for all youth during pandemic times.